Measurement of validity and reliability of Bengali-translated Incontinence Severity Index questionnaire - Shamima Islam Nipa; Thanyaluck Sriboonreung; Aatit Paungmali; Chailert Phongnarisorn (Bulletin of Faculty of Physical Therapy, 2024)
Abstract Objective The purpose of the study was to verify the psychometric properties of the Bengali-translated Incontinence Severity Index (ISI) questionnaire. Materials and methods A test–retest data collection method was conducted with 47 respondents using the Bengali-translated ISI questionnaire. Results The mean age of the respondents was 41.4 years; standard deviation (S.D.) ± 9.90. Most of the women were suffering with moderate severity of urinary incontinence 48.9% (n = 23). The present study determined that Bengali-translated ISI questionnaire was valid and reliable. In addition, present study reflected on the content validity of the Bengali version of ISI questionnaire was 1 > 0.75; internal consistency α = 0.80 and intra-class correlation (ICC) = 0.86 respectively. Conclusion The Bengali version of ISI questionnaire is valid and reliable measurement tool to extent the severity of urinary incontinence in the cultural context of Bangladesh.